Tonic modulation of anxiety-like behavior by corticotropin-releasing factor (CRF) type 1 receptor (CRF1) within the medial prefrontal cortex (mPFC) in male mice: Role of protein kinase A (PKA) - Miguel, Tarciso Tadeu [UNESP]; Games, Karina Santos [UNESP]; Nunes-de-Souza, Ricardo Luiz [UNESP] (Elsevier B.V., 2014)
The medial prefrontal cortex (mPFC) and the neuropeptide corticotropin-releasing factor (CRF) have recently been receiving more attention from those interested in the neurobiology of anxiety. Here, we investigated the CRF pathway in the modulation of anxiety-like behaviors in male mice exposed to the elevated plus-maze (EPM), through intra-mPFC injections of CRF, CP376395 [N-(1-ethylpropyl)-3,6-dimethyl-2-(2,4,6-trimethylphenoxy)-4-pyridinamine hydrochloride, a CRF type 1 receptor antagonist (CR F1)] or H-89 [N-[2-[[3-(4-bromophenyl)-2-propenyl]amino]ethy11-5 Aso quinolinesulf onamide dihydrochloride, a protein kinase (PICA) inhibitor]. We also investigated the effects of intra-mPFC injections of H-89 on the behavioral effects induced by CRF. Mice received bilateral intra-mPFC injections of CRF (0, 37.5, 75 or 150 pmol), CP376395 (0, 0.75, 1.5 or 3 nmol) or H-89 (0, 1.25, 2.5 or 5 nmol) and were exposed to the EPM, to record conventional and complementary measures of anxiety for 5 mm. Results showed that while CRF (75 and 150 pmol) produced an anxiogenic-like effect, CP376395 (all doses) and H-89 (5 nmol) attenuated anxiety-like behavior. When injected before CRF (150 pmol), intra-mPFC H-89 (2.5 nmol, a dose devoid of intrinsic effects on anxiety) completely blocked the anxiogenic-like effects of CRF. These results suggest that (i) CRF plays a tonic anxiogenic-like role at CRF1 receptors within the mPFC, since their blockade per se attenuated anxiety indices and (ii) the anxiogenic-like effects following CRF1 receptor activation depend on CAMP/PICA cascade activation in this limbic forebrain area. (C) 2014 Elsevier Inc All rights reserved.
Keywords: Anxiety; Corticotrophin-releasing factor (Cm); CRF1 receptor; PKA; Medial prefrontal cortex (mPFC); Elevated plus maze; Mice